1977
DOI: 10.3382/ps.0561777
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobins In Some Galliformes Birds

Abstract: In several groups of galliform birds (chicken, turkey, pheasant and guinea fowl) the presence and function of plasma haptoglobin (Hp) have been studied. Paper, acetate and starch-gel electrophoresis were carried out and two benzidine stain regions were observed when haemoglobin (Hb) was added to normal plasma (Hb-Hp complex and methemalbumin) besides the free Hb when the binding capacity of these proteins were surpassed. The disappearance of the administered Hb-59Fe was exponential which is evidence of the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It has been reported that a r antitrypsin, fibrinogen, and haptoglobin increase (Conner et al, 1988;Taira et al, 1992) in mammals that were injected with turpentine. In birds, Musquera and Planas (1977) reported increase of haptoglobin. Delers et al (1983) detected c^-acid glycoprotein, but they did not refer to other proteins.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that a r antitrypsin, fibrinogen, and haptoglobin increase (Conner et al, 1988;Taira et al, 1992) in mammals that were injected with turpentine. In birds, Musquera and Planas (1977) reported increase of haptoglobin. Delers et al (1983) detected c^-acid glycoprotein, but they did not refer to other proteins.…”
Section: Discussionmentioning
confidence: 96%